Literatur Review Tentang Manajemen Konflik : Definisi, Tujuan, Sumber, dan Model Pengelolaan Konflik - Iftitah Khoirina Savitri; Fita Ardianti Rohmah; Danial Atiq Ma’shum; Mohammad Rizal Fauzi; Mualimin Mualimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article aims to provide a comprehensive understanding of conflict management through a review of the literature related to definitions, objectives, sources, and models of conflict management. Conflict in organizations is unavoidable and can have positive or negative impacts depending on how the conflict is managed. This research uses the literature study method to analyze various conflict management concepts that have been put forward by experts. The results of the study show that conflict management aims to minimize the negative impact of conflict and maximize positive outcomes through fair and constructive resolution. Sources of conflict in organizations can come from differences in interests, and differences in values and perceptions between individuals or groups. Various conflict management models such as collaboration, transformational, and mediation are identified as approaches that can be applied in different situations to achieve effective resolution. With a deeper understanding of conflict management, organizations can be better equipped to manage internal tensions and improve productivity and working relationships among members.